EU foreign investment law - Dimopoulos, Angelos (Oxford : Oxford University Press, 2011)
Regulation of foreign investment is one of the most topical and controversial subjects in EU law and international investment law. This book examines the legal foundations upon which EU investment policy is based, addressing the legal, practical, and political concerns created by the establishment of a common investment policy.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Investments, Foreign -- Law and legislation -- European Union countries